Diagnostic and prognostic value of procalcitonin for early intracranial infection after craniotomy - Yu,Y. (2017)
Intracranial infection is a common clinical complication after craniotomy. We aimed to explore the diagnostic and prognostic value of dynamic changing procalcitonin (PCT) in early intracranial infection after craniotomy. A prospective study was performed on 93 patients suspected of intracranial infection after craniotomy. Routine peripheral venous blood was collected on the day of admission, and C reactive protein (CRP) and PCT levels were measured. Cerebrospinal fluid (CSF) was collected for routine biochemical, PCT and culture assessment. Serum and CSF analysis continued on days 1, 2, 3, 5, 7, 9, and 11. The patients were divided into intracranial infection group and non-intracranial infection group; intracranial infection group was further divided into infection controlled group and infection uncontrolled group. Thirty-five patients were confirmed with intracranial infection after craniotomy according to the diagnostic criteria. The serum and cerebrospinal fluid PCT levels in the infected group were significantly higher than the non-infected group on day 1 (P<0.05, P<0.01). The area under curve of receiver operating characteristics was 0.803 for CSF PCT in diagnosing intracranial infection. The diagnostic sensitivity and specificity of CSF PCT was superior to other indicators. The serum and CSF PCT levels have potential value in the early diagnosis of intracranial infection after craniotomy. Since CSF PCT levels have higher sensitivity and specificity, dynamic changes in this parameter could be used for early detection of intracranial infection after craniotomy, combined with other biochemical indicators.